Episodic venting of extreme subsalt overpressure through a thick evaporitic seal. (August 2022) - Kirkham, Chris; Cartwright, Joe; James, David; Kearney, Luke
Abstract: Episodic venting from deep overpressured layers has rarely been documented in sedimentary basins, so the pressure evolution leading to these cyclical phenomena is poorly understood at present. Using three-dimensional (3D) seismic data from the West Nile Deep Sea Fan, we interpret >480 fluid escape pipes within a region of prolific leakage across a > 2 km thick sealing sequence of salt and claystones. Within this region, we map five linear trails of pipes with pockmarks or small mud volcanoes at their outlets and interpret them to have formed by episodic venting of overpressured fluids from beneath the salt, over a ∼2–3 Myr period, coeval with basinward displacement of the pipes by flow of the salt. Importantly, the pipe trails root to the crests of stratigraphic traps at the base of the salt seal. Direct measurements from nearby exploration wells are used to construct pressure-depth and pressure-time plots over the lifetime of the pipe trails and demonstrate that overpressure near to or in excess of the lithostatic pressure must be repeatedly achieved in the stratigraphic traps to breach the salt seal every 50–150 kyrs. This pressure evolution is best described by a sawtooth pattern with overpressure relieved by venting, followed by re-seal of the trap, and pressure recharge. The pressure recharge for this episodic venting can most easily be explained here by biogenic gas generation and aquifer pressure transfer in the traps, with some minor contribution from sustained disequilibrium compaction during the Pliocene to Recent. The conditions necessary for this type of episodic venting should occur more widely, particularly in basins with thick evaporite deposits. The recognition of episodic venting has important implications for prospect de-risking, drilling safety and CO2 and hydrogen storage. Highlights: Episodic venting through the thick evaporitic seal in the Eastern Mediterranean. Multi-episode linear pipe trails form by repeated hydraulic fracturing through the evaporitic seal. Erosional stratigraphic traps at the base-salt produce overpressured pre-salt compartments that the pipe trails root to and present a significant drilling hazard. The pressure evolution in the traps during the lifetime of the pipe trails is expressed by a sawtooth pressure evolution. A combination of biogenic gas generation, pressure transfer and disequilibrium compaction recharges pressure in the traps.